Hukuman Mati Dalam Lingkaran Kontroversi Etis Kristen - Melyarmes H. Kuanine (Sekolah Tinggi Teologi Sabda Agung, Surabaya, 2019)
In the implementation of the death sentence is not a sentence given as a criminal offender sentenced to life imprisonment. However, the death penalty is the loss of a person's life due to an error proven guilty based on a court decision (jurisprudence). This right to life maps the death penalty as an ethical issue. The most noble right in life as a gift from God, the applicable legal regulations also place human life in a valuable position both in their roles and positions as well as in their social responsibilities or legal responsibilities and also regarding their rights and obligations. From this impact arose the pros and cons of both secular people and in Christianity itself. The researcher determines a qualitative descriptive method for studying, collecting and compiling data through literature studies that relate to the paradigm of the death penalty in a circle of Christian ethical controversy. Therefore, this article will describe the elements of power, love, truth and justice as the government's duty in showing its identity to enforce the execution of the death penalty and will explain the Christian ethical attitude and perspective of the Christian community towards the execution of the death penalty. Abstrak Dalam pelaksanaan hukuman mati bukanlah hukuman yang diberikan sebagai pelaku kejahatan dihukum dengan penjara seumur hidup. Namun hukuman mati merupakan penghilangan nyawa seseorang akibat kesalahan yang terbukti bersalah berdasarkan keputusan pengadilan (jurisprudensi). Hak hidup inilah memetakan hukuman mati sebagai persoalan etis. Hak tersebut paling mulia dalam kehidupan sebagai pemberian Tuhan, peraturan hukum yang berlaku juga menempatkan hidup manusia pada posisi yang berharga baik dalam peran dan posisi maupun dalam tanggung jawab sosial atau tanggng jawab hukumnya dan juga menyangkut hak maupun kewajiban-kewajibannya. Dari dampak ini pun timbul pro dan kontra baik orang sekuler maupun dalam kekristenan sendiri. Peneliti menentukan metode deskriptif kualitatif untuk mempelajari, mengumpulkan dan menyusun data melalui studi pustaka yang berhubungan dengan paradigma hukuman mati dalam lingkaran kontroversi etika Kristen. Oleh karena itu, artikel ini akan menguraikan unsur-unsur kekuasaan, kasih, kebenaran dan keadilan sebagai tugas pemerintah dalam memperlihatkan jatidirinya untuk menegakkan pelaksanaan hukuman mati dan akan menjelaskan sikap etis Kristen dan perpektif masyarakat Kristen terhadap pelaksanaan hukuman mati.